2021
DOI: 10.1039/d1dt03105h
|View full text |Cite
|
Sign up to set email alerts
|

Surface phosphorization of Ni–Co–S as an efficient bifunctional electrocatalyst for full water splitting

Abstract: The surface phosphorization of NiCo2S4 make it exhibit superior electrochemical activity, which is ascribed to the modulation of electronic structure, the rise of conductivity, the promotion of electrochemical surface area and the active sites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 39 publications
1
11
0
Order By: Relevance
“…In general, the OER process can be described by the four-step mechanism and three adsorption intermediates OH*, O*, and OOH*, 52 indicating that CuMoO 4 @Co 3 O 4 is transformed into hydroxide in the OER process, and hydroxide is considered as an active substance to improve the performance of OER greatly. 25 As displayed by the Raman spectra in Fig. S4 † (catalyst after OER stability test), the peak at 351 cm −1 belongs to CuO bending vibration, the peak at 642 cm −1 is attributed to Co 3 O 4 , and the peaks at 805 and 933 cm −1 pertain to CuMoO 4 corresponding to the MoO 4 tetrahedron's tensile vibration mode.…”
Section: Papermentioning
confidence: 97%
See 1 more Smart Citation
“…In general, the OER process can be described by the four-step mechanism and three adsorption intermediates OH*, O*, and OOH*, 52 indicating that CuMoO 4 @Co 3 O 4 is transformed into hydroxide in the OER process, and hydroxide is considered as an active substance to improve the performance of OER greatly. 25 As displayed by the Raman spectra in Fig. S4 † (catalyst after OER stability test), the peak at 351 cm −1 belongs to CuO bending vibration, the peak at 642 cm −1 is attributed to Co 3 O 4 , and the peaks at 805 and 933 cm −1 pertain to CuMoO 4 corresponding to the MoO 4 tetrahedron's tensile vibration mode.…”
Section: Papermentioning
confidence: 97%
“…Therefore, it is greatly necessary to develop other types of catalysts with both low expense and super performance toward water splitting. 25,26 Research shows that the electrochemical capability of mixed metal oxides is better than that of single metal oxides due to the high electrochemical activity and redox activity of electron transitions between metals of different valence. 27,28 Furthermore, heterogeneous structure engineering was also proposed, 29 and it was found that the synergistic effect between components in heterogeneous catalysts could promote the electrocatalytic reaction process.…”
Section: Introductionmentioning
confidence: 99%
“…After 595 cycles, the ΔE value of K-DMO is raised to 0.80 V, which could be blamed on surface reconstruction. 56 For comparison, the noble metal battery displays a worse ΔE value of 0.79 V in the first cycle and a deteriorated ΔE value of 0.93 V in the 595th cycle. In terms of cycling stability, GCD tests were continued until the batteries failed or 1000 cycles were completed.…”
Section: Rechargeable Zinc-air Battery Performancesmentioning
confidence: 99%
“…Transition-metal sulfides (TMSs) have been used as promising electrode materials for supercapacitors and water splitting due to their abundant redox reaction sites, low electronegativity, and flexible phase structure. , Liu et al synthesized a p-doped Ni-Co-S@C with a high specific capacity of 1026 C/g at 1 A/g via a one-step solvothermal approach and a phosphorization process. Yang et al synthesized a P-doped NiCo 2 S 4 on carbon fiber paper through a hydrothermal and phosphorization reaction, which showed an HER overpotential of 176 mV and an OER overpotential of 265 mV at 10 mA/cm 2 . However, the TMSs alone still cannot meet the requirements for applications because of their poor rate capability, cycling stability, slow reaction kinetics, and large volume change during the charge–discharge process …”
Section: Introductionmentioning
confidence: 99%
“…Yang et al synthesized a P-doped NiCo 2 S 4 on carbon fiber paper through a hydrothermal and phosphorization reaction, which showed an HER overpotential of 176 mV and an OER overpotential of 265 mV at 10 mA/cm 2 . However, the TMSs alone still cannot meet the requirements for applications because of their poor rate capability, cycling stability, slow reaction kinetics, and large volume change during the charge–discharge process …”
Section: Introductionmentioning
confidence: 99%